Unveiling the influence of CeO2 rare-earth oxide content on in-situ phase formation and properties of aluminium matrix composites - Erol, Mahmut; Bayrak, Yahya; Kisasoz, Burcin Ozbay; Yilmaz, Mustafa Alper; Ozkan, Dogus; Kisasoz, Alptekin (ELSEVIER SCI LTD, 2025)
In this study, the hot pressing technique was used to produce Al-CeO2 composites. Furthermore, the effects of CeO2 content on in-situ phase formation and the properties of the composites were systematically investigated. The samples were fabricated at 600 degrees C at 1, 5 and 10 wt% CeO2 content. The in-situ phases could not be observed at 1 and 5 wt% CeO2 ratios. However, intermetallic phases and complex oxides like Al11Ce3 and Al11CeO18 were identified in the sample containing 10 wt% CeO2. It was revealed that 5 wt% CeO2 containing composite exhibited superior wear resistance and the wear rate of the aluminium was decreased from 9.851.10-4 mm3/Nm to 2.562.10-4 mm3/Nm. It was observed that the in-situ formed oxide deteriorated the wear properties of the composite, and the wear resistance of Al-CeO2-10 was reduced. Also, increasing CeO2 content provided the formation of in-situ oxides and stabilized the surface. Accordingly, the wear rate of the aluminium was improved up to 0.0548 mm/year owing to the existence of 10 wt% CeO2. The surface stability of the composite was enhanced with CeO2 particles, and the corrosion damage shifted the CeO2 and complex oxides containing regions.
Keywords: Hot pressing (A); Composites (B); Corrosion (C); CeO2 (D); MECHANICAL-PROPERTIES; MICROSTRUCTURE; ALLOY; Materials Science